Análisis de herramientas forenses aplicado a dispositivos Android. - Garces Muñoz, Angeli Tamara (2024)
This-study examines the effectiveness of forensic tools used on Android devices, focusing on Andriller and AFLogical OSE. The objectives include a literature review of digital forensics and its applications on Android, identifying key forensic tools and evaluating their effectiveness in recovering digital evidence. Topics covered include digital forensics, stages and objectives of forensics, digital evidence, cybercrime, Android and how it works, forensic analysis on mobile devices. Tools such as Andriller, AFLogical OSE, Cellebrite UFED, FTK Imager and Magnet AXIOM were reviewed, but the actual testing focused mainly on Andriller and AFLogical OSE. The results show that both tools are effective in collecting and analyzing data from Android devices, although they have limitations depending on data type and device state. Andriller excels at extracting data from specific applications, while AFLogical OSE shows excellent performance in collecting logs and system communications. This study concluded that the combined use of various forensic tools can improve the accuracy and coverage of digital evidence collection. It also emphasizes the importance of constantly updating forensic tools and techniques to adapt to technological advances and new threats. These findings provide practical guidance for forensic investigators on the selection and use of forensic tools on Android devices.